Mitochondrial toxicity and caspase activation in HIV pregnant women. Issue 1 (30th August 2016) - Hernandez, Sandra; Moren, Constanza; Catalán‐García, Marc; Lopez, Marta; Guitart‐Mampel, Mariona; Coll, Oriol; Garcia, Laura; Milisenda, Jose; Justamante, Angela; Gatell, Josep Maria; Cardellach, Francesc; Gratacos, Eduard; et al.
Abstract: To assess the impact of HIV‐infection and highly active anti‐retroviral treatment in mitochondria and apoptotic activation of caspases during pregnancy and their association with adverse perinatal outcome. Changes of mitochondrial parameters and apoptotic caspase activation in maternal peripheral blood mononuclear cells were compared at first trimester of pregnancy and delivery in 27 HIV‐infected and ‐treated pregnant women versus 24 uninfected pregnant controls. We correlated immunovirological, therapeutic and perinatal outcome with experimental findings: mitochondrial DNA (mtDNA) content, mitochondrial protein synthesis, mitochondrial function and apoptotic caspase activation. The HIV pregnancies showed increased adverse perinatal outcome (OR: 4.81 [1.14–20.16]; P < 0.05) and decreased mtDNA content (42.66 ± 5.94%, P < 0.01) compared to controls, even higher in naïve participants. This depletion caused a correlated decrease in mitochondrial protein synthesis (12.82 ± 5.73%, P < 0.01) and function (20.50 ± 10.14%, P < 0.001), not observed in controls. Along pregnancy, apoptotic caspase‐3 activation increased 63.64 ± 45.45% in controls ( P < 0.001) and 100.00 ± 47.37% in HIV‐pregnancies ( P < 0.001), in correlation with longer exposure to nucleoside analogues. HIV‐infected women showed increased obstetric problems and declined genetic and functional mitochondrial parameters during pregnancy, especially those firstly exposed to anti‐retrovirals. The apoptotic activation of caspases along pregnancy is emphasized in HIV pregnancies promoted by nucleoside analogues. However, we could not demonstrate direct mitochondrial or apoptotic implication in adverse obstetric outcome probably because of the reduced sample size.